Blasting resistance of curved sandwich composite concrete bunkers - Mahmudul, Hasan; Ahmad Kueh, Beng Hong (Techno-Press, 2024)
Improving the blast resistance of structural establishments has become an imperative engineering commitment to prevent property damage and fatalities in terrorist incidents. This study investigates the effects of blast mass and stand-off distance on CFRP skin concrete core sandwich bunkers of varying thicknesses using ABAQUS/Explicit software with CONWEP functionality. The considered parameters include TNT masses of 1, 10, and 25 kg and stand-off distances of 0.1, 1, 2, and 2.5 meters on structures with 200, 250, and 500 mm core thicknesses. The study finds that there exists a declining response corresponding to the blasting mass reduction coupled with increases in the stand-off distance and core thickness. The 500 mm thick bunker sustains less damage compared to those with 200 mm and 250 mm core thicknesses. The sandwich configuration remains structurally advantageous vs. those without skins. The sandwich bunker with a 500 mm thick concrete core gives the best performance against the 10 kg TNT blast load with a 1 m standoff distance exhibiting a 22.8% reduction in damage vs. that without skins. Mathematical expressions are then formulated for predicting maximum von Mises stress, principal stress, and displacement of sandwich bunkers as functions of TNT masses, stand-off distances, and core thicknesses.